Por entre as brechas dos muros da universidade: O circo como componente curricular na formação inicial em Educação Física - Rita de Cassia Fernandes Miranda; Eliana Ayoub (Universidade do Minho, 2017)
This descriptive research examines the ramifications of curriculum implementation of the circus as a component in the initial training in Physical Education in institutions of higher education of the State of São Paulo/Brazil. Narrative interviews to teachers, administrators and students were made to a total of 13 participants. Viewing the curriculum as a territory of disputes and power relations, the intense participation of teachers and students in teaching, research and extension has given visibility to the circus in the production of new knowledge. The study highlights the important role assumed by study and research groups that are active in these institutions, encouraging many students graduating today, as well as teachers, to incorporate this knowledge in elementary school, in social projects, among other professional contexts, some of them including groups with an artistic focus. However, the examples investigated do not constitute a majority of the Brazilian national reality, something that could be mapped by other investigations.